The Effect of Emotional Intelligence Education on the Prevention of Adolescent Delinquency in Indonesia - Maryati Tombokan; Naharia Laubo; Rahman; Hafni Van Gobel; Muh. Ardi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: The research objective was to determine the differences in the emotional intelligence level of vocational school (VHS) students before and after being given education on adolescent delinquency prevention in Gowa, South Sulawesi Province, and Gorontalo, Gorontalo Province. Method: Pre Experiment research method with Two Group Pre Test and Post Test Control Design. Sampling with purposive sampling with a total number of respondents 110 people. Data collection used a questionnaire to measure emotional intelligence and identify the form of adolescent delinquency using a Likert scale, data analysis using Wilcoxon analysis to see the level of emotional intelligence before education, and Mann-Whitney analysis test, after education. Result: The results showed that there were differences before and after education in VHS Gowa students, but there was no difference in emotional intelligence before and after education on VHS Gorontalo students, there was no difference in Emotional Intelligence between the intervention and control groups before and after education and there was no difference. student delinquency both in the intervention group and control group before and after emotional intelligence education. Conclusion: The recommendations that can be given are the importance of parental supervision of students, especially in choosing friends to do activities outside the home, and cross-sectoral cooperation is needed in promotive and preventive efforts supervision and control of all forms of adolescent or student delinquency.